2010
DOI: 10.1007/s10704-009-9439-z
|View full text |Cite
|
Sign up to set email alerts
|

A study aimed at determining and understanding the fracture behaviour of an Al–Li–Cu–Mg–Zr alloy 8090

Abstract: The S-L fracture toughness of aluminiumlithium based alloys is generally poor and this has limited their applicability, particularly in aerospace where good damage tolerance is required. The low S-L toughness has been attributed variously to grain boundary precipitation, planar slip and lithium segregation. This work examined the S-L fracture behaviour of an 8090 Al-Li-based alloy in 34-45 mm plate. The results confirmed that the S-L fracture toughness decreases from the centre to the surface of plate material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Besides, the cost of Al-Li alloys is higher than that of traditional Al alloys because of the ageing conditions and comparable strength. Therefore, various studies have been carried out to investigate metal forming technologies (i.e., hydroforming, impact hydroforming, stamping, bending, and superplastic forming) under different working conditions (i.e., cold, warm, and hot deformation) to identify an alternative manufacturing route and to optimize the working conditions to decrease the higher costs related to the addition of Li and the manufacturing of sound, complex shape components from Al-Li alloys [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the cost of Al-Li alloys is higher than that of traditional Al alloys because of the ageing conditions and comparable strength. Therefore, various studies have been carried out to investigate metal forming technologies (i.e., hydroforming, impact hydroforming, stamping, bending, and superplastic forming) under different working conditions (i.e., cold, warm, and hot deformation) to identify an alternative manufacturing route and to optimize the working conditions to decrease the higher costs related to the addition of Li and the manufacturing of sound, complex shape components from Al-Li alloys [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the differences in these two grain structures (of recrystallised and unrecrystallised AA8090) are shown in Figure 5. Bregianos, Crosky, Munroe and Hellier (2010) describe the dispute within the literature as to the reason for low fracture toughness. It has been attributed to: slip planarity (Blankenship, Hornbogen, & Starke, 1993), i.e.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Lithium segregation involves brittle intergranular failure when the lithium concentration at the grain boundaries is above a certain level, and ductile intergranular failure occurs below it. While Bregianos et al (2010) found evidence to support aspects of each model in their experimental work, indicating that the dispute remains today. When Al-Li alloys are compared with conventional aluminium alloys in notched highcycle fatigue testing, the results are generally favourable (Wanhill, 1994).…”
Section: Mechanical Propertiesmentioning
confidence: 99%